High antisite defect concentrations in hard-sphere colloidal Laves phases. Issue 17 (8th April 2020) - van der Meer, Berend; Smallenburg, Frank; Dijkstra, Marjolein; Filion, Laura
Abstract : We show that the equilibrium Laves phase in binary hard-sphere mixtures contains an extraordinarily high concentration of antisite defects: we find stable regions where up to 2% of the large-particle lattice sites are occupied by a small particle. Abstract : Binary mixtures of hard spheres can spontaneously self-assemble into binary crystals. Computer simulations have been especially useful in mapping out the phase behaviour of these mixtures, under the assumption that the stoichiometry of the binary crystal is ideal. Here we show that for a size ratio of q = 0.82 this assumption is not valid near the coexistence region between the fluid and the stable binary crystal, the MgZn2 Laves phase. Instead we find a surprisingly high number of antisite defects: up to 2% of the large spheres are replaced by small spheres in equilibrium. We demonstrate that the defect concentration can be estimated using simple approximations, providing an easy way to identify systems where antisite defects play an important role. Our results shed new light on the self-assembly of colloidal Laves phases, and demonstrate the importance of antisite defects in binary crystals.